ChemInform Abstract: Intermolecular Ketene—Alkene [2 + 2] Cycloadditions: The Significance of Lewis Acid Promoted Variants. Issue 25 (24th June 2014) - Rasik, Christopher M.; Brown, M. Kevin
Abstract Review: [27 refs.